Análisis de las tendencias de consumo en las generaciones Baby Boomers, X, Millennials y Z. Caso Loja-Ecuador - Mantilla Quinde, Rosa Gabriela (2023)
This research aims to analyze the different consumption trends in the Baby Boomers, X, Millennials and Z generations of the city of Loja, in order to identify their tastes and preferences at the time of consumption, since not all generations have the same habits, tastes and preferences, within this research five variables were taken into account the same as food, technology, leisure, education and health. In order to obtain information from these generations, a survey was conducted with 400 people where it was stratified by generations, that is, 100 surveys to each generation, the results obtained in this research were analyzed through the IBM SPSS program, the research was conclusive exploratory, thus resulting in differences and similarities in the four generations that were investigated as l accessibility to education, preferences in terms of consumption and how they acquire certain products or services and similarities in medication, food and housing. One of the differences that was found in the generations was the use of technology, an example is the Baby Boomers generation, 34% use the radio more, the X 41% use the cell phone more, the Millennials 47% use the cell phone more and the Z generation 47% use the cell phone more.